2022
DOI: 10.1038/s41467-022-30357-w
|View full text |Cite|
|
Sign up to set email alerts
|

An Artificial Intelligence-guided signature reveals the shared host immune response in MIS-C and Kawasaki disease

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is an illness that emerged amidst the COVID-19 pandemic but shares many clinical features with the pre-pandemic syndrome of Kawasaki disease (KD). Here we compare the two syndromes using a computational toolbox of two gene signatures that were developed in the context of SARS-CoV-2 infection, i.e., the viral pandemic (ViP) and severe-ViP signatures and a 13-transcript signature previously demonstrated to be diagnostic for KD, and validated our findings in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 90 publications
2
38
0
1
Order By: Relevance
“…We not only formally define the nature of that host response and provide computational tools to measure the extent of such response, but also chart the cascade of cytopathic changes in the alveoli that are critical for the profibrogenic state. It is noteworthy that the same host immune response is seen also in MIS-C, a new disease that co-emerged with COVID-19, and in KD (which shares overlapping features with MIS-C in clinical presentation 35 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We not only formally define the nature of that host response and provide computational tools to measure the extent of such response, but also chart the cascade of cytopathic changes in the alveoli that are critical for the profibrogenic state. It is noteworthy that the same host immune response is seen also in MIS-C, a new disease that co-emerged with COVID-19, and in KD (which shares overlapping features with MIS-C in clinical presentation 35 ).…”
Section: Discussionmentioning
confidence: 93%
“…PIMS-TS). 35 To avoid overreliance on one set of signatures (i.e., ViP/sViP, which are tissue-agnostic signatures of host response), and increase the specificity for lung tissue, an independent gene signature was included, one that is induced in COVID-19 lung tissues, but not in influenza. 13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the report by Delaye et al shows that higher hepcidin levels are critical in patients with COVID-19 compared to in non-COVID-19 patients with similar CRP levels [ 50 ]. Growing evidence has revealed that multisystem inflammatory syndrome associated (MIS-C) with COVID-19 in children shares many clinical features [ 51 ] and inflammatory responses with KD [ 52 ]. Until now, there is no result of hepcidin in MIS-C, and it is worth further research.…”
Section: Discussionmentioning
confidence: 99%
“…Particular genetic determinants may also play a role as rare inborn errors of immunity altering the immune response to SARS-CoV-2 have been highlighted as possible pathogenetic factors of MIS-C in some children [24 ▪▪ ]. An artificial intelligence-guided signature revealed a host immune response shared between MIS-C and Kawasaki disease [25].…”
Section: Multisystem Inflammatory Syndrome In Childrenmentioning
confidence: 99%